Reduced glomerular and elevated tubulointerstitial transglutaminase pathway and its inhibition in a rat model of renal warm ischemia: implications for feline chronic kidney disease - Sánchez-Lara, A. C.; Maamra, M.; Haylor, J. L. (Frontiers in Veterinary Science, 2025)
IntroductionFeline CKD is associated with an increase in the pro-fibrotic enzyme, transglutaminase 2 (TG2), in the kidney tubulointerstitium. Hypoxia is pivotal factor for the development of CKD, irrespective of its origin. In cats, tubulointerstitial sclerosis develops without significant glomerular involvement, similar to a rodent model of renal warm ischaemia (RWI).MethodsSprague-Dawley rats underwent 60-min renal hilar clamping followed by right nephrectomy with/without intrarenal infusion of a transglutaminase inhibitor (TGI). Renal fibrosis was assessed by immunofluorescence of collagens after 28-days. Extracellular-TG-enzyme activity (eTGact) and extracellular-TG2 protein (eTG2) were measured in both the glomerular and the tubulointerstitial spaces.HypothesisRenal Warm Ischemia (RWI) will induce fibrotic changes and activation of the transglutaminase pathway in both the tubulointerstitial and glomerular compartments, and that treatment with a transglutaminase inhibitor (TGI) will mitigate these effects.ResultsRats subjected to RWI showed a significant elevation in tubulointerstitial collagen I (1.8-fold), III (4.3-fold), IV (5.5-fold), eTGact (2-fold) and eTG2 (1.9-fold), together with an increase in serum creatinine (2.7-fold). TG inhibition significantly reduced tubulointerstitial collagen I, III, IV, eTGact and eTG2 by 100%, 57%, 90%, 89%, and 91%, respectively, and decreased creatinine levels by 70%. However, RWI in the glomerulus showed a significant reduction in the TG pathway and collagen I and IV.DiscussionOur findings support a causal link between TG2 and tubulointerstitial fibrosis in rats following RWI. In contrast, the glomerular TG-pathway was suppressed, suggesting a protective mechanism in response to RWI, which may help to explain the lack of glomerular involvement in feline CKD. This rodent model of RWI may be analogous to feline CKD, enabling extrapolation of findings from rodent RWI models to understand renal insult in cats.